OP0168 Nik-ikk complex interaction controls nf-Κb-dependent inflammatory activation of the endothelium in response to ltΒr ligation. (12th June 2018) - Jeucken, K.; Kucharzewska, P.; Maracle, C.X.; van Hamburg, J.P.; Olsson, H.K.; Tas, S.W.
Abstract : Background: Sites of chronic inflammation, such as rheumatoid arthritis (RA) synovial tissue, are characterised by neovascularization and often contain tertiary lymphoid structures with characteristic features of lymphoid organs such as high endothelial venules (HEV), and sometimes even true germinal centres. Ligation of the lymphotoxin (LT)-β receptor (LTβR) results in activation of both canonical and NF-κB-Inducing Kinase (NIK)-dependent noncanonical NF-κB signalling in endothelial cells (EC) and plays a crucial role in lymphoid neogenesis. Noncanonical NF-κB signalling in EC promotes inflammation-induced angiogenesis and triggers the development of the cuboidal HEV appearance. However, the relative contribution of the individual pathways to the acquisition of leukocyte traffic-regulating properties by EC is less well understood. Objectives: To identify the molecular pathways by which LTβR drives inflammatory activation of EC to promote interactions with leukocytes. Methods: Primary human EC were treated with LTβ or LIGHT to activate LTβR, followed by analysis of downstream NF-κB signalling pathways and expression of inflammatory cytokines and adhesion molecules. To repress canonical NF-κB signalling pathway, a small molecule inhibitor of IKKβ was used, and noncanonical NF-κB signalling was repressed with siRNA targeting NFκB2. The role of NIK in LTβR signalling was investigated using small molecule inhibitors and siRNA targeting NIK, as well as adenoviral overexpression of NIK. The role of NF-κB signalling in RA was measured by stimulating EC with RA synovial fluid (RASF) followed by analysis of inflammatory mediators. Results: LTβR triggering in EC resulted in activation of both canonical and noncanonical NF-κB signalling pathways and induced inflammatory cytokine expression and immune cell adhesion. IKKβ inhibition completely repressed LTβR-induced inflammatory activation of EC, indicating that this process was mediated through canonical NF-κB signalling. Interestingly, inactivation of NIK with small molecule inhibitors and siRNAs significantly decreased LTβR-induced expression of inflammatory cytokines and adhesion of immune cells to endothelium, whereas silencing of NFκB2 had no effect. This suggests that the noncanonical pathway is dispensable for NIK-dependent activation of EC through the canonical NF-kB pathway. Further analyses, including silencing of NIK and NIK overexpression, demonstrated a role for NIK in activation of the canonical NF-kB pathway by amplifying IKK complex activity. RASF stimulation of EC resulted in activation of canonical and noncanonical NF-κB signalling, and increased the expression of inflammatory cytokines and adhesion molecules, which could be blocked by targeting NIK. Conclusions: These findings suggest that in addition to regulating noncanonical signalling, NIK can serve as an amplifier of canonical NF-κB signalling and associated inflammatory responses in EC, which may play a role in development and maintenance of chronic inflammation. Consequently, NIK may be an attractive therapeutic target. Disclosure of Interest: K. Jeucken: None declared, P. Kucharzewska Employee of: AstraZeneca, C. Maracle: None declared, J. P. van Hamburg: None declared, H. Olsson Employee of: AstraZeneca, S. Tas: None declared